POLITICAL ELITES OF THE COLLECTIVE WEST ON THE FRONTS AND IN THE TRENCHES OF THE COLD WAR WITH RUSSIA - P. L. Karabuschenko (Современная наука и инновации, 2022)
In recent years, Russophobia has reached its new historical heights, which makes us look at this phenomenon of political life as yet another aggravation of the collective West against Russia in the Cold War. Since the XVI century russophobia is an integral part of the "crusade" declared by the West against Russia, the purpose of which is to subordinate this Eastern European "monster". The maximum program of this campaign provided for the dismemberment and complete destruction of Russia as a state, as a cultural and historical community. To a large extent, the modern Russophobian tradition copies the accumulated during these five centuries experience of creating a negative image of a potential adversary, even in peacetime, representing him as an insidious enemy, who is carrying out frankly evil intentions.